Women, Ordination, and a Buddhist Perspective: A Violation of Rights? - Roloff, Carola (Religious studies and theology, 2017)
Taking women’s ordination - a main gender issue debated in Buddhism - as an example, I reason why discrimination against women in religion not only violates women’s human rights but also basic Buddhist principles such as non-violence. I question whether from a Buddhist perspective religion and rights are two mutually exclusive terms, and then discuss two areas of tension: a tension between religious and secular law, on the one hand, and a tension between religious freedom and gender equality, on the other. Based on this, I analyse how the dynamics of these areas of tension and gender issues could become a driving force for interreligious dialogue and for dialogue between religions and secular societies.